THE MEDIATING ROLE OF SOCIAL INFORMAL LEARNING IN THE RELATIONSHIP BETWEEN HIGH INVOLVEMENT HUMAN RESOURCE PRACTICE AND LEARNING CLIMATE ON EMPLOYABILITY OF STARTUP COMPANY EMPLOYEES - Ayu, Dewi Sekar; Martdianty, Fanny (Jurnal Aplikasi Manajemen, 2023)
Startup companies undergo many changes to deal with changing economic conditions and win the competition in the market. One of the factors that can increase company competitiveness is employability of the employee. This study combines organizational structural factors, namely the application of highly involved human resources and learning culture with employee factor namely social informal learning. The research aims to identify the factors that can enhance or hinder social informal learning and subsequently improve employee employability in startups. Purposive sampling technique was used to select the participants who met specific criteria relevant to the research objectives. Data from 290 employees of Indonesian startups analyzed using a structural equation model. The results showed that recognition, empowerment, competitive development, information sharing can enhance social informal learning and subsequently improve employee employability, while financial rewards can decrease social informal learning and employability. Companies that want to increase the practice of social informal learning can improve recognition practices, empowerment, competitive development, and informaÂtion sharing.